Improving Critical Thinking Skill of Junior High School Students through Science Process Skills Based Learning - Diego Pradana; Mohamad Nur; Nadi Suprapto (Jurnal Penelitian Pendidikan IPA, 2020)
This study aimed to investigate impact the science process skill-based learning on critical thinking skills of Junior High School students. Subjects were eighth grade students of Rengel Junior High School 1 that were selected by purposive random sampling. Measurement data by means of science process skills test and critical thinking skill test was analyzed by using inferential statistical one-tailed t-test and linear regression. The results showed that implementation of science process skill-based learning was effective to improve the critical thinking skill of Junior High School student